1979
DOI: 10.1136/bmj.2.6194.819
|View full text |Cite
|
Sign up to set email alerts
|

Value of emergency toxicological investigations in differential diagnosis of coma.

Abstract: Summary and conclusionsOut of 208 cases of coma of unknown aetiology referred to the poisons unit of this hospital during 1978 for emergency toxicological investigations, 108 were found to be due to self-poisoning. Medical conditions, mainly neurological, accounted for coma in 90 patients; the cause was not ascertained in the remaining 10 cases. More than one preparation had been ingested by 58 (54%) of the poisoned patients, although barbiturates were the drugs most commonly encountered in the severe cases.To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(11 citation statements)
references
References 14 publications
(4 reference statements)
0
11
0
Order By: Relevance
“…It is claimed that an inaccurate diagnosis is not affecting mortality (8,12), nor being the cause of complications (13). However, knowing the correct diagnosis could enable optimal treatment of acute poisoning by reducing the need for supervision and costly treatments, and facilitating the identification of cases that require prompt drug-specific treatment (10,12,13,17). Thus, both morbidity and costs may be reduced.…”
Section: Introductionmentioning
confidence: 95%
“…It is claimed that an inaccurate diagnosis is not affecting mortality (8,12), nor being the cause of complications (13). However, knowing the correct diagnosis could enable optimal treatment of acute poisoning by reducing the need for supervision and costly treatments, and facilitating the identification of cases that require prompt drug-specific treatment (10,12,13,17). Thus, both morbidity and costs may be reduced.…”
Section: Introductionmentioning
confidence: 95%
“…Complete reversal of coma occurred within ten minutes of administration in 49 patients. Full toxicological screening (Helliwell et al, 1979) in 45 identified ethanol at a mean plasma concentration of 3.54g/l (range 2.40-5.90 g/1) as the sole cause of unconsciousness in 38 cases; phenobarbitone (21 mg/1) was the only drug present in addition to ethanol (3.1 g/1) in a further patient. Dextropropoxyphene was the agent responsible for coma in the other 6 patients in addition to alcohol.…”
Section: Methods and Resultsmentioning
confidence: 98%
“…In the second part of this study we assessed the role for naloxone in cases in which the NPIS were requested to carry out toxicological screening (Helliwell et al, 1979). Sixty-four requests were made when opiates were suspected of contributing to the coma, either from circumstantial evidence, e.g.…”
Section: Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specimens of blood (10 ml) and urine (20 ml) were requested in the latter stages of the survey in order to provide objective confirmation of the diagnosis. The specimens were analysed for a wide range of drugs by a combination of colour tests, thin-layer and gas chro matography [Helliwell et al, 1979].…”
Section: Methodsmentioning
confidence: 99%